الإسلام والتعددية الدينية: دراسة تحليلية في التعددية الدينية في إندونيسيا - Alfina Hidayah Malik (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2019)
This paper discusses the concept and discourse of religious pluralism globally and in the context of Indonesians in particular. Where the discourse of religious pluralism has entered into the discourse of Islamic thought in Indonesia on a massive scale since the 70s. In this article, the author tries to compare and analyze the notion of religious pluralism in the context of classical Islam with contemporary Islamic thought using literature studies; both classical and contemporary Islamic literature relating to the discourse of religious pluralism. From this discussion at least the researcher can conclude the following findings; 1) the term religious pluralism is not known in the discourse of classical Islamic thought, it is only included in the study of Muamalah; 2) Religious pluralism is an understanding taken from the Western worldview and does not have roots in the treasury of Islamic thought, 3) the imposition of religious pluralism in the context of Islam and Indonesians is not appropriate because it is contrary to Islamic and Indonesian characteristics.